1992
DOI: 10.1007/bf00695986
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of mitomycin A, mitomycin C, and sevenN 7 analogs in vitro

Abstract: The alkylating antitumor agents mitomycin A (MMA), mitomycin C (MMC), and seven N7 analogs were compared in terms of their cardiotoxic and antitumor activity in vitro. Neonatal rat-heart myocytes were sensitive to five of the compounds studied, including MMA, 7-dimethylamidinomitosane (BMY-25282), 7-(N-methyl-piperazinyl)-mitosane (RR-194), N7-(4-iodophenyl)-MMC (RR-208), and N7-(4-hydroxyphenyl)-MMC (M-83) in order of descending molar potency. MMA and RR-208 possessed the greatest cytotoxic potency against 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Typically, MA derivatives were 2 orders of magnitude more potent than the corresponding MC derivatives . Furthermore, a significant correlation was observed between in vitro cardiotoxicity and redox potential, MA being 3 orders of magnitude more cardiotoxic than MC to rat heart cells …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Typically, MA derivatives were 2 orders of magnitude more potent than the corresponding MC derivatives . Furthermore, a significant correlation was observed between in vitro cardiotoxicity and redox potential, MA being 3 orders of magnitude more cardiotoxic than MC to rat heart cells …”
Section: Discussionmentioning
confidence: 97%
“…Mitomycin A (MA; 1b ), which differs from MC only in its 7-substituted group (7-methoxy instead of 7-amino), exhibited high toxicity in experimental animals, which prevented its clinical use. Furthermore, MA is several orders of magnitude more cytotoxic to tumor cells than MC. , Extensive SAR studies established that mitomycins with 7-alkoxy substituents had higher redox potentials than 7-nitrogen-substituted mitomycins (e.g., E 1/2 of MA and MC are −0.19 and −0.40 V, respectively) and that a strong correlation existed between E 1/2 and the activity of these mitomycins. ,
1
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Haemolytic-uraemic syndrome can occur and is particularly likely in patients who receive a cumulative dose of over 60 mg (Martino et al, 1979;Ratanatharathom et al, 1979;Rabadi et al, 1982). Preclinical studies have shown that BMS-181174 is cardiotoxic in rats, although not in mice or dogs (Dorr et al, 1992). In our phase I study we saw some evidence of impairment of cardiac function as measured by changes in LVEF.…”
Section: Discussionmentioning
confidence: 50%
“…There have also been reports of pulmonary fibrosis, nephrotoxicity and haemolytic-uraemic syndrome (Carter and Crooke, 1979;Rabadi et al, 1982). MMC is cardiotoxic in animals and in patients when given with or after doxorubicin (Dorr et al, 1992). The clinical use of MMC is limited by these toxicities and by the emergence of drug resistance.…”
mentioning
confidence: 99%